Perceived consequences and worries among youth in Norway during the COVID-19 pandemic lockdown. - Lehmann, Stine; Skogen, Jens Christoffer; Haug, Ellen; Mæland, Silje; Fadnes, Lars Thore; Sandal, Gro Mjeldheim; Hysing, Mari; Bjørknes, Ragnhild (Scandinavian Journal of Public Health, 2021)
Aims: To examine perceived consequences for everyday life, learning outcomes, family relations, sleep problems and worries for infection, for friends and their future, among youth aged 12–19 years during weeks 7 to 9 of the COVID-19 lockdown in Norway. We examine variations by age, gender, socioeconomic status and country of birth. Methods: Youth within the municipality of Bergen were invited via SMS to participate in a 15-minute online survey. A total of 2997 (40%) youths participated. The mean age was 17 years (standard deviation 1.7). Results: Overall, 28% reported feeling somewhat to a lot impacted by schools closing, 63% reported learning less. In total, 62% reported improvement of everyday life. The youth's situation in their family was worse for 13%. Regarding sleep problems, 19% reported difficulties initiating and maintaining sleep, 12% had more nightmares, while 90% reported later bedtime and rise time. Seven per cent worried about getting infected, while 53% worried about infection among family members. A total of 19% worried that the outbreak would lead to a more difficult future, and 32%worried that friends were facing a difficult situation at home. Perceived consequences and worries related to the lockdown varied across sociodemographic groups. Conclusions : The perceived consequences and degree of worries varied by age, gender, socioeconomic status and to a certain degree country of birth. Girls, older youth, youth with lower socioeconomic status and with a migrant background from developing countries seemed to experience the lockdown as more difficult, and thereby possibly accentuating the need for services in these groups.